A SURVEY ON STRATEGIES TO MITIGATE HOT SPOT PROBLEM IN WIRELESS SENSOR NETWORKS - Pearl; Datta, Subhasis; Tiwari, Kamalika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The imbalance of energy consumption of the nodes in Wireless Sensor Networks causes some nodes to die prematurely leading to network partitions. The nodes near the base station suffer from such a problem called the “hot spot problem or energy hole problem”. These nodes die due to heavy load on them to relay other nodes’ traffic towards the base station. Hence an important issue in the design of wireless sensor networks is to beat this problem. This paper reviews all of the proposed solutions to overcome the hot spot problem.